INFORMATION TECHNOLOGY RESPONSES AND FINANCING ABILITY ON E-COMMERCE PERFORMANCE - Ompusunggu, Lis Sintha; Simbolon, Ika Pratiwi (International Journal of Research -GRANTHAALAYAH, 2020)
This research objective is to recalling the paradigm and describe the various responses to use information technology. This research is a type of literature study. This study is also descriptive research with the support of theories and the findings from previous studies. Responses to new technologies and financing ability play an essential role in achieving good performance. Strategic responses are different among firms that can be classified according to magnitude, domain, and speed. IT strategy, IT structure, social media and search engine marketing also other responses which have essential roles to the firm’s performance.